Training Needs of Farm Women in Vegetables Cultivation in Hilly Areas (Indian Journal of Extension Education, 2011)
In hilly state of Uttarakhand, the role of farm women in agricultural operations become important due to several unique factors like migration of males to plains in search of jobs, small land holding and less mechanization of agriculture. The present study was undertaken in Bageshwar district of Uttarakhand to assess the training needs of farm women for vegetable cultivation technology. It was assessed that farm women most needed training in areas like knowledge of improved varieties, disease and IPM, spacing, seed treatment, weed control, cropping system, marketing, package of practices, management of fertilizers, quality improvement and nursery raising. The study concludes that the practices like sowing time, harvesting, seed rate, intercultural operation, irrigation and use of organic manures in which farm women received training contributed major role in reducing overall knowledge gap.